Evaluation of Sperm Parameters and DNA Integrity Following Different Incubation Times in PVP Medium - Nabi, Ali; Entezari, Farahnaz; Miresmaeili, Seyed Mohsen; Vahidi, Serajoddin; Lorian, Keivan; Anbari, Fatemeh; Motamedzadeh, Leila (Urology Journal, 2021)
Purpose: Polyvinylpyrrolidone (PVP) is a chemical material used in intracytoplasmic sperm injection (ICSI) program. The aim of this study was to investigate the ideal time that sperm can be safely incubated in PVP with less structure and DNA damage. Method: Thirty-one Oligoasthenoteratospermia (OAT) samples were used. Sperm samples were prepared by discontinuous density-gradients method and incubated in 10% PVP at different time intervals (0, 5, 10, 15, 20, and 30 min). The effect of PVP was assessed on sperm DNA fragmentation and viability via SCD assay and Eosin–nigrosin staining respectively. Results: Data showed there was a significant increase in sperm DNA fragmentation at 10 min compared to 0 min. The viability rate also significantly reduced at 10 min compared to 0 min. Conclusion: As a result, sperm samples could be incubated with PVP for less than 10 min. While prolonged incubation may significantly damage the sperm DNA integrity and viability.